2014
DOI: 10.1002/hed.23523
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic predictors of recurrence and overall survival in adenoid cystic carcinoma of the head and neck: A single institutional experience at a tertiary care center

Abstract: Background The purpose of this study was to determine factors that impact recurrence and long-term survival of head and neck adenoid cystic carcinoma (ACC). Methods We conducted a retrospective review of 87 patients with head and neck ACC who were evaluated between 1992 and 2009. Staining for Ki-67, p53, α-estrogen receptor (αER), and progesterone receptor (PR) was performed. Results Forty men (46%) and 47 women (54%) were included in this study. Median follow-up for patients was 98 months. Five-year recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 30 publications
7
41
3
Order By: Relevance
“…In the present study, advanced age (that is >60 years) did not affect dfs, implying that age alone does not modify the natural history of acc. The parotid and other salivary glands, followed by the oro-nasopharyngeal spaces, were the most common sites of origin, consistent with the literature 11,28,29 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, advanced age (that is >60 years) did not affect dfs, implying that age alone does not modify the natural history of acc. The parotid and other salivary glands, followed by the oro-nasopharyngeal spaces, were the most common sites of origin, consistent with the literature 11,28,29 .…”
Section: Discussionsupporting
confidence: 88%
“…Female sex did not affect survival in our cohort. The data related to female sex as a prognostic factor are conflicting: A study based on the U.S. National Cancer Institute's Surveillance, Epidemiology, and End Results database suggested improved os; another study showed a worse dfs, even after matching for stage 2,28 . Although hormones or other sex-dependent biologic factors might explain a greater female:male ratio, whether the same factors affect disease behaviour or outcomes is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The known predilection of ACC for perineural invasion, and the association of PNI with disease recurrence,(2, 3) adds importance to our finding that the axonal guidance signaling pathway is significantly altered in ACC. Somatic mutations of genes involved in axonal guidance signaling (including NTNG1, SEMA3G, and SEMA5A ) were also previously noted by Ho et al ,(5) and an identical SEMA3G non-synonymous substitution (474S>P) was observed in our cohort.…”
Section: Discussionmentioning
confidence: 61%
“…(1) ACC frequently spreads to nearby nerves, a process termed perineural invasion (PNI), which portends poor prognosis and higher likelihood of local recurrence. (2, 3) There are at present no reliable chemotherapeutic options for long-term disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, gender does not represent a factor of prognostic significance for survival [1,8] ( Table 3). Although cribriform and solid histologic subtypes are the most frequently identified patterns in this and other studies' their significance as prognostic factors does not enjoy a widely spread consensus [9]. Nevertheless, a multivariate analysis performed by Da Cruz Perez et al [1], found that solid type was a significant prognostic factor and, similarly, Van Weert et al [10] confirmed that the solid type or Grade III is related to a significantly worse outcome, possibly because it is a higher grade tumor with a more aggressive growth pattern and a tendency for early development of distant metastasis.…”
Section: Discussionmentioning
confidence: 64%